Bacteriophage Therapy Against Antimicrobial Resistant Crisis - Ullah, Fahim; Ahmad, Syed Sohail; Khan, Mazhar Ali; Moon, Sarwat (Journal of Health Science and Medical Therapy, 2024)
The most common virus on the earth is bacteriophage (or phages) that are present in all organisms. Their classification is currently being evaluated based on the phage's unique and antibacterial properties. The phage replicates within the host through a lytic or lysogenic process following infection and use of a bacterial cell machine. Phage has become an effective therapeutic drug against pathogens after twort and Filex d'Herelle discovery of bacteriophage in the 1900s, and subsequent research has been conducted. Nevertheless, bacteriophage therapy has become an unavoidable option for research due to the recent occurrence of bacterial antibiotics resistance. Around fifty years after antibiotic were found, antibiotics resistance is key risk for health care. Antimicrobial resistance is a rising big issue in global healthcare. The WHO, 1st report on antimicrobial resistances globally, has emphasized the threat of a forthcoming post antibiotics age, where little infection could be not treatable and once again will be fatal. Considering the present condition, producing therapeutic agent that are complementary to antibiotics play great role to fight against antibiotic resistance. The crisis requires development and implementation of new therapeutic agents against infections and phage therapy is suitable to control infectious diseases because safety of phage therapy. There is a perception with regards to phage therapy that phages are usually safe, on the bases of fact that they are ubiquitous in nature and our continued contact to phages in the environment and furthermore that they are widely used without adverse effects in many of the world. with this positive interpretation, the application of phage therapy must be verified by current research studies. bacteriophage preparations contain detrimental substances, such as toxins of gram-negative bacteria, during the formulation process of bacteriophage and that can be remove by different purification methods. Phages effects normal flora GIT negligibly due to specificity in nature and they infect only a small number of bacterial species.